Multiple-Criteria Decision Analysis and characterisation of phase change materials for waste heat recovery at high temperature for sustainable energy-intensive industry. (15th January 2020) - Royo, Patricia; Ferreira, Victor J.; Ure, Zafer; Gledhill, Sam; López-Sabirón, Ana M.; Ferreira, Germán
Abstract: A latent heat storage system based on Phase Change Materials (PCMs) is proposed to increase the energy and environmental efficiency by recovering and storing waste heat from combustion gases or other surplus sources at in the energy-intensive industries (EII), currently unused. The final configuration design is specifically adapted to the plant operational requirements, by means of a methodology combining the search of the best conceptual design and a proper selection of core PCMs. To that end, a selection of suitable PCM is carried out by using characterisation techniques and thermal stability testing. Furthermore, relevant key factors are weighted by an in-house Multiple-Criteria Decision Analysis (MCDA) to define the most promising design options to be implemented in two plants belonging to the EII sector. For the ceramic sector, the design resulted in a shell-and-tube system with 1188 kg of a PCM melting at 885 °C and encapsulated in double concentric tubes, involving a storage capacity of 227 MJ. Similarly, 1606 kg of PCM, whose phase-change temperature is 509 °C, is selected for the steel sector providing a PCM-TES system capable to store 420 MJ. Graphical abstract: Image 1 Highlights: A phase-change material system is proposed working at high temperature for waste heat recovery. Thermal characterisation and cycling were conducted on the candidate storage material. Two phase change materials are identified for the application with a high latent heat capacity and thermal stability. A multiple-criteria decision analysis defined shell and double concentric tubes storage as the most suitable configuration.